1995
DOI: 10.1088/0954-0083/7/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Study of the polymerization of high-performance polymers by electrons and x-rays: 2. The case of bismaleimide/N-vinylpyrrolidone

Abstract: In the context of radiation-induced polymerization of bismaleimide monomers, we have investigated the polymerization mechanisms and kinetics of a bismaleimide/vinyl-pyrrolidone system. Several parameters were considered, including the type of dose (electrons or x-rays), power, presence of a catalyst and the carbon fibre filler. To this end, we developed a methodology based on physicochemical studies by infrared absorption spectroscopy and solid state 3CNMR (CP-MAS) in order to quantify the chemical species cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The T g of the final product is 200°C. The above reaction conversions and T g of BMI/NVP products are close to those reported by Grenier‐Loustalot et al,30 who cured the modified BMI/NVP resin by 400 kGy at 50 kGy per step. Also, the conversion results support our earlier conclusion that initiators do not affect the cure conversion of the final products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The T g of the final product is 200°C. The above reaction conversions and T g of BMI/NVP products are close to those reported by Grenier‐Loustalot et al,30 who cured the modified BMI/NVP resin by 400 kGy at 50 kGy per step. Also, the conversion results support our earlier conclusion that initiators do not affect the cure conversion of the final products.…”
Section: Resultsmentioning
confidence: 99%
“…E‐beam curing is found to be insufficient to cure BMI resin 30. The addition of reactive diluents into the BMI resin system can increase the reactivity of BMI during E‐beam curing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The E-beam curing studies were carried out using 4,4 0 -bismaleimidodiphenylmethane/BMI-1,3-tolyl/ o,o 0 -diallylbisphenol A-based BMI systems. Grenier-Loustalot et al 20 made a successful attempt at using NVP as a diluent for E-beam curing of BMI resins. 21 It has been reported that the percentages of residual maleimide functions in BMI/NVP systems are less than 10%, and the glass transition temperatures of the cured products are around 240 C after a 400 kGy E-beam dose at 50 kGy per pass.…”
Section: Introductionmentioning
confidence: 99%